From Peel to Paper: Nutritional Characterization and Biodegradable Paper Production from Musa Paradisiaca Banana Peels - Ibtisam Abu Bakar; Nur Hanim Aqilla Suhaimi; WAHIDA ABDUL RAHMAN (Journal of Applied Science & Process Engineering)
Musa Paradisiaca is a variety of bananas used mainly for cooking instead of being consumed fresh. The peel of bananas, which is frequently seen as a byproduct, holds valuable nutritional and industrial potential. The nutritional banana peel can be applied and transformed into a beneficial product. This research aimed to characterise the nutritional content of the banana peel of Musa Paradisiaca and produce paper from it. The banana peel was analysed for its nutritional content across different ripening stages. The results showed that the nutritional content in the banana peel varies depending on the maturity stages, with unripe peels having the highest dry matter and fat content, ripe peels having the highest moisture, crude fibre, and protein content, and overripe peels having the highest ash content. Moreover, the total sugar content increases during the ripe stage due to enzymatic conversion to starch, and the total phenolic content of the ripe peel is at 7.93 mg GAE/g, indicating strong antioxidant properties in the peel. The paper made from the ripe peel is pale yellow with a rough texture and moderate flexibility compared to regular paper. Furthermore, ATR-FTIR analysis of the derived paper indicates that the presence of functional groups contributes to the paper’s structural integrity. Additionally, the tensile strength of the paper exhibited moderate tensile strength and rigidity. The study indicated a 36.9% weight loss after 10 days in a soil burial experiment, indicating rapid biodegradation of derived paper from ripe Musa Paradisiaca peel.